Summer state of mind - Calonita, Jen (Poppy/Little, Brown and Company, 2014)
"Spoiled, yet lovable fifteen-year-old Harper McCallister is sent to sleepaway camp where she is an outcast at first but eventually finds a way to make her mark, gaining new perspectives on friendship and life in general"--